2018
DOI: 10.37134/ejsmt.vol5.2.2.2018
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing Habits of Mind (HOM) Through Thinking Based Learning (TBL) in Doing Science Technology, Engineering and Mathematics (STEM) Project

Abstract: Habits of mind (HOM) is one of the kind response to those questions and problems whereby the answers to which are not immediately known which can attribute to effective problem solvers and critical thinking development. However, the emphasis on this aspect is still low especially among science educators as well as secondary science students which in the long run will retard the production of knowledge worker who are able to behave when confronted with life's problems. The study addressed the integration of Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
0
0
1
Order By: Relevance
“…[41] through integrated science learning STEM can give the impression of an interesting and not boring learning. The results of this study are also in line with Hashim, Ali, and Samsudin [42]. They found that the habits of the mind depend on the classroom environment, a good learning environment, where teachers are responsible for providing a good learning environment and develop productive habits of mind.…”
Section: Resultssupporting
confidence: 88%
“…[41] through integrated science learning STEM can give the impression of an interesting and not boring learning. The results of this study are also in line with Hashim, Ali, and Samsudin [42]. They found that the habits of the mind depend on the classroom environment, a good learning environment, where teachers are responsible for providing a good learning environment and develop productive habits of mind.…”
Section: Resultssupporting
confidence: 88%
“…Hasil dapatan ini boleh dijelaskan dengan kajian Di (2016) (1950) yang menyatakan sesuatu pembelajaran berlaku apabila ia berkaitan dengan realiti (dipetik daripada Hashim et al, 2018). Hujahan ini juga disokong oleh Iriani et al (2019) serta Zhao dan Beckett (2014) yang menyatakan pelajar mengaplikasikan rangkai kata serta tatabahasa yang dipelajari dalam projek berdasarkan topik pembelajaran.…”
Section: Perbincanganunclassified